10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Postoperative delirium (POD) occurs as a significant complication after elective surgery. OBJECTIVE: To investigate the modulation of delirium incidence by transcranial electric stimulation (tES). DESIGN, SETTING, AND PARTICIPANTS: A double-blind, sham-controlled randomized clinical trial (Modulating Delirium Through Stimulation [MODEST]) was conducted at University Medicine Greifswald, Germany, from February 8, 2024, to January 15, 2025. Patients were aged 65 years or older who were scheduled to undergo elective surgery. Exclusion criteria were any history of neurological or psychiatric disease, or intake of central nervous system-active medication. Data were analyzed from June 10, 2025, to June 5, 2026. INTERVENTION: α-Transcranial alternating current stimulation (tACS) of the salience network, transcranial direct current stimulation (tDCS) of the frontoparietal network (dosing: 20 minutes, 2 mA), or sham, in the postanesthesia care unit (PACU) after major elective surgery. MAIN OUTCOMES AND MEASURES: The primary outcome was POD incidence in the ward during 1 of up to 5 postoperative days for the comparison of tACS vs the sham group. The secondary outcomes included POD in the ward for the comparison of tDCS vs sham group, POD in PACU, POD severity and motor type, and postoperative pain. Prespecified subgroup analyses opted to test the dependence of POD incidence on age, sex, duration, and type of surgery, baseline cognitive function, and preoperative pain levels. RESULTS: A total of 225 patients (mean [SD] age, 73.0 [6.0] years; 59.6% [134] male) were randomly assigned to tACS (n = 68), tDCS (n = 83), or sham stimulation (n = 74). No substantial between group differences were observed for POD incidence in ward (tACS, 11.5% [6 of 52]; tDCS, 14.3% [9 of 63]; sham, 9.2% [6 of 65]; tACS vs sham: odds ratio [OR], 1.60 [95% CI, 0.47-5.46]; P = .45; tDCS vs sham: OR, 1.51 [95% CI, 0.49-4.68]; P = .47) or in PACU (tACS, 14.6% [7 of 48]; tDCS, 21.4% [12 of 56]; sham, 21.7% [13 of 60]; tACS vs sham: OR, 0.95 [95% CI, 0.38-2.36]; P = .91; tDCS vs sham: OR, 0.91 [95% CI, 0.36-2.30]; P = .83). Further secondary analyses of POD severity and motor type, and modulation of pain levels, did not show any substantial difference between stimulation groups. Prespecified subgroup analyses revealed different modulation of POD incidence in PACU depending on duration of surgery (OR, 0.15 [95% CI, 0.02-0.97]; P = .046), indicating that tACS may reduce POD incidence for patients with longer surgery (absolute risk difference for POD in the tACS compared with the sham group, for a surgical duration of 3 to 5 hours of -26.6% to -46.5%). Ratings of adverse events did not differ between groups (incidence rate ratio, 2.3 [95% CI, 0.8-6.5]), and no serious adverse events were reported. CONCLUSIONS AND RELEVANCE: In this randomized clinical trial of tES for POD, there was no evidence for a uniform effect of postoperative tES on the incidence of POD, but it suggested a benefit of parietal α oscillatory enhancement for patients with longer surgery. Future research has to test the specific effect on vulnerable groups, examine the optimal timing for tES application to modulate POD, and investigate the value of personalizing tES parameters. TRIAL REGISTRATION: German Clinical Trials Register: DRKS00033703.